2011
DOI: 10.1097/icb.0b013e3181f66aac
|View full text |Cite
|
Sign up to set email alerts
|

Kyrieleis Plaques Associated With Acute Retinal Necrosis From Herpes Simplex Virus Type 2

Abstract: Kyrieleis plaques have been found in the setting of toxoplasmosis, tuberculosis, syphilis, rickettsial disease, herpes zoster virus, intraocular lymphoma, and idiopathic branch retinal artery occlusions. The differential diagnosis for these periarterial plaques should also include herpes simplex virus type 2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Their occurrence in ARN is rare. There is a single case report of Kyrieleis plaques in ARN due to HSV-2, 8 and two reports in ARN due to VZV 9, 10. To the best of our knowledge, this is the first report of Kyrieleis plaques in ARN due to HSV-1.…”
Section: Discussionmentioning
confidence: 76%
“…Their occurrence in ARN is rare. There is a single case report of Kyrieleis plaques in ARN due to HSV-2, 8 and two reports in ARN due to VZV 9, 10. To the best of our knowledge, this is the first report of Kyrieleis plaques in ARN due to HSV-1.…”
Section: Discussionmentioning
confidence: 76%
“…Only few cases have been reported in literature [ 4 ]. This rare condition has been reported particularly in association with infectious posterior uveitis: toxoplasmosis [ 5 ], syphilis [ 6 ], Mediterranean spotted fever [ 7 ], acute retinal necrosis due to HSV-2 [ 8 ], and VZV [ 9 ], but has also been described in posterior uveitis with inflammatory origin: Behçet disease and sarcoidosis [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pichi et al conducted a multimodal imaging study of 25 eyes with Kyrieleis arteritis and suggested that Kyrieleis plaques represent an inflammatory process within the vessel wall and most probably the endothelium. Full-thickness involvement of the vessel wall is highly unlikely, as indicated by the absence of leakage in fluorescein angiography [ 8 , 9 ]. Kyrieleis arteriolitis has primarily been associated with ocular toxoplasmosis, but it has also been described in tuberculosis, syphilis, acute retinal necrosis, cytomegalovirus retinitis and Mediterranean spotted fever as well as in noninfectious diseases such as Behçet’s disease and Susac’s syndrome [ 10 , 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%